2015
DOI: 10.5194/hess-19-4831-2015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of near-surface soil moisture assimilation at subseasonal, seasonal, and inter-annual timescales

Abstract: Abstract. A 9 year record of Advanced Microwave Scanning Radiometer -Earth Observing System (AMSR-E) soil moisture retrievals are assimilated into the Catchment land surface model at four locations in the US. The assimilation is evaluated using the unbiased mean square error (ubMSE) relative to watershed-scale in situ observations, with the ubMSE separated into contributions from the subseasonal (SM short ), mean seasonal (SM seas ), and inter-annual (SM long ) soil moisture dynamics. For near-surface soil moi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Draper and Reichle (2015) have shown that data assimilation is able to correct modelled soil moisture also at longer time intervals from subseasonal to seasonal scale and seasonal differences in the assimilation effect are reported across many studies, as also shown here. Existing hydrological monitoring systems, such as the US Drought Monitor (Svoboda et al, 2002), the African Flood and Drought Monitor , the German Drought Monitor (Samaniego et al, 2013) or the Australian Water Resource Assessment (Van Dijk et al, 2011;Vaze et al, 2013) all use soil moisture quantiles at grid cell level to characterise different levels of severity and facilitate the comparison of soil moisture levels between grid cells.…”
Section: Discussionmentioning
confidence: 52%
“…Draper and Reichle (2015) have shown that data assimilation is able to correct modelled soil moisture also at longer time intervals from subseasonal to seasonal scale and seasonal differences in the assimilation effect are reported across many studies, as also shown here. Existing hydrological monitoring systems, such as the US Drought Monitor (Svoboda et al, 2002), the African Flood and Drought Monitor , the German Drought Monitor (Samaniego et al, 2013) or the Australian Water Resource Assessment (Van Dijk et al, 2011;Vaze et al, 2013) all use soil moisture quantiles at grid cell level to characterise different levels of severity and facilitate the comparison of soil moisture levels between grid cells.…”
Section: Discussionmentioning
confidence: 52%
“…On average, the assimilation resulted in slightly higher skill improvements against the surface in situ measurements for DA-NN and DA-L2P-gCDF and slightly higher skill improvements in the root zone for DA-NN-lCDF. Overall, the results suggest that the global rescaling approaches could potentially be very beneficial for soil moisture estimation under the conditions of: (1) a good observation error characterization; (2) rigorous observation quality control; and (3) potential component-wise assimilation [51] to better isolate the reliable satellite information.…”
Section: Discussionmentioning
confidence: 93%
“…To use the DA-NN approach it is thus crucial to accurately characterize the model and observation errors and to apply a rigorous quality control to the observations. Additionally, to better isolate the reliable retrieval information, it might be beneficial to separately assimilate the different temporal components of the retrievals-i.e., the long-term mean, seasonal, sub-seasonal and interannual signatures [51]-with the DA-NN approach.…”
Section: Discussion Of Da-nn and Da-nn-lcdf Resultsmentioning
confidence: 99%
“…In this study a land surface model is combined with PMW Tb observations in a data assimilation (DA) approach. The ultimate goal of DA is to yield a merged estimate that is superior to the observations and to the model alone (Draper & Reichle, 2015;Forman & Margulis, 2010;McLaughlin, 2002;Reichle, 2008). The direct assimilation of Tbs (rather than PMW-derived SWE retrievals) is preferable as it avoids inconsistencies in the use of In order to overcome the spatial sparsity in ground-based measurements, other studies assimilated satellite-based retrieval products to characterize SWE or snow depth, which are derived from either physical (e.g., radiative transfer) or statistical (e.g., regression) models.…”
Section: Introductionmentioning
confidence: 99%